2021
DOI: 10.1007/s40617-021-00577-5
|View full text |Cite
|
Sign up to set email alerts
|

Black Caregivers’ Perspectives on Racism in ASD Services: Toward Culturally Responsive ABA Practice

Abstract: Significant racial and ethnic disparities in health care and service access exist. In the present article, we reviewed qualitative studies investigating the racism-related experiences of Black caregivers of children with autism spectrum disorder (ASD) in the U.S. health care system. Specifically, we examined institutional racism (i.e., systemic racism) and individual racism directed toward Black families when they seek diagnoses and services for their children with ASD. Additionally, we summarized culturally r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Racial match between Black families and clinicians can help with early identification, as Black clinicians may more easily recognize references, speech patterns, or preferences that are culturally inappropriate, repetitive, or restricted interests (Davenport et al, 2018). Black clinicians can also address barriers to Black youth receiving an autism diagnosis, like racism that manifests in primary care screening/referrals (Dababnah et al, 2018) and navigating services in predominately non-Black spaces (Čolić et al, 2021). Future research should consider the role of IPC and racial match in Black patients’ care utilization trajectories, especially at the intersection of gender and sex, given the historical exclusion of Black girls from the literature (Lovelace et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Racial match between Black families and clinicians can help with early identification, as Black clinicians may more easily recognize references, speech patterns, or preferences that are culturally inappropriate, repetitive, or restricted interests (Davenport et al, 2018). Black clinicians can also address barriers to Black youth receiving an autism diagnosis, like racism that manifests in primary care screening/referrals (Dababnah et al, 2018) and navigating services in predominately non-Black spaces (Čolić et al, 2021). Future research should consider the role of IPC and racial match in Black patients’ care utilization trajectories, especially at the intersection of gender and sex, given the historical exclusion of Black girls from the literature (Lovelace et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although Li et al (2019) provided data on faculty salaries in behavior analysis according to gender, and Vance and Saini (2022) provided data on salaries of practitioners that are certified by the BACB according to gender and race/ethnicity, data on differences in remuneration of certificants by gender, geographic locations served, and age groups served (particularly children) are not available. An emphasis on geographic locations served by BCBAs and BCBA-Ds is necessary, as some research has shown that children with ASD who receive ABA-based services and reside in metropolitan (i.e., urban) areas have greater access to BCBAs (Yingling et al, 2021a(Yingling et al, , b, 2022, while other research has shown that white families living in geographic areas with higher median household incomes have increased availability of behavior-analytic services and that access to ABA-based services is affected by structural racism (Broder-Fingert et al, 2020;Čolić et al, 2021). As a result of the discrepancies in these results, further research on pay disparities is needed, especially for maintaining culturally responsive services for children living in impoverished/disenfranchised communities.…”
Section: Impacts Of Pay Inequitiesmentioning
confidence: 99%
“…Within-subject designs using similar methods to evaluate participants' outcomes over time can have meaningful impact in the contemporary field of behavior analysis. There has been increasing attention in using behavior analytic principles to address social issues such as systematic racism (Shea et al, 2022), as well as critical reflections on the research and clinical practice of behavior analysis among the Black community (Čolić et al, 2022;Lovelace et al, 2022). Čolić et al (2022) synthesized black caregivers' experience when it comes to autism care and provided specific accounts on racism manifested across its multiple stages.…”
Section: Figurementioning
confidence: 99%
“…The current social and political environment often has placed the field of behavior analysis in its crosshairs. We are increasingly being described as a field of insensitive determinants of client autonomy (Kirkham, 2017;McGill & Robinson, 2021), responsible for the development of alleged trauma in former clients (Kupferstein, 2018), insensitive to racial injustices (e.g., Čolić et al, 2022;Zarcone et al, 2019), and behind trends of interest that need to be more fully addressed and analyzed (e.g., DeFelice & Diller, 2019;Fontenot et al, 2019;Kornack et al, 2019;Morris et al, 2021;Wang et al, 2019). Even our most heavily dominated applied appendage -autistic care -is being challenged as non-effective (United States of America Department of Defense, 2021).…”
Section: Introductionmentioning
confidence: 99%